DATABASES AND ELECTRONIC LIBRARIES IN LEARNING ENGLISH - Zarina S. Khaytmuratova; Gavhar A. Salomova (Bright Mind Publishing, 2025)
This article examines the importance of databases and electronic libraries in learning English. The research methodology includes literature review and statistical analysis. The findings demonstrate the effectiveness of resources and the opportunities they provide for learners.
Keywords: English language, databases, electronic libraries, teaching methods, educational effectiveness, information resources, learning process, digital platforms, knowledge acquisition opportunities.